ANALISIS MANAJEMEN KAS DAN SEKURITAS TERHADAP LIQUIDITAS PADA PT MNC SKY VISION TBK - Nidia Anggreni Das; Aisyah Putri; Afchelllya anugrah Putri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This research is motivated by the liquidity challenges faced by the digital media sector due to post-pandemic revenue fluctuations. The study aims to conduct an in-depth analysis of the influence of cash management and marketable securities management on the liquidity level of PT MNC Vision Networks Tbk (IPTV), listed on the Indonesia Stock Exchange (IDX), based on the 2024 financial reporting period. The research methodology employed is descriptive quantitative, analyzing secondary data from audited consolidated financial statements. Data analysis techniques include financial ratio analysis—specifically the Current Ratio and Cash Ratio—as well as horizontal analysis to observe trends in current asset changes. The results indicate that the company’s cash and cash equivalents experienced a significant decrease of 40.5%, dropping from Rp233,029 million in 2023 to Rp138,647 million in 2024, driven by negative operating cash flows. Simultaneously, marketable securities management—specifically other financial assets in the form of equity securities on the IDX—recorded a 9.9% decline in fair value to Rp640,031 million. Consequently, the company’s liquidity position (Current Ratio) stood at 0.58x, indicating that current assets are insufficient to cover short-term liabilities totaling Rp2.75 trillion. The study concludes that while the company’s strategy of maintaining a securities portfolio serves as an emergency liquidity buffer, more rigorous debt restructuring and operational efficiency are required to improve the internal cash position. The implications of this research emphasize the importance of synergy between receivables conversion and timely divestment of securities to maintain business continuity amidst high liquidity risks.